Manejo da fertilização NK em plantio de eucalyptus urophylla em solo de cerrado - Silva, Alexandre Costa da [UNESP] (2015)
The planted area of eucalyptus in Mato Grosso do Sul continues to expand; however, production costs have increased, especially fertilizer, thus, reducing the profitability of producers. In this context, it was aimed to evaluate the growth of eucalyptus clone I-144 and its nutritional status according to the application of nitrogen, phosphorus and potassium and split-application of N and K 2 O, in sandy soil in Cerrado, with low rates of P and K. The experiment was performed at the Renascença Farm, agricultural fund managed by Cargill Agricola S/A, located in Três Lagoas/MS. It was arranged in a randomized complete blocks experimental design with six treatments and five replications. The treatments were the following: T1 (control - without NPK); T2 (standard rate, the split-application of N and K 2 O, in 3 applications); T3 (reduced rate, the split-application of N and K 2 O, in 2 applications); T4 (standard rate, the split-application of N and K 2 O, in 2 applications); T5 (reduced rate of N and K 2 O, in 1 application) and T6 (standard rate of N and K 2 O, in 1 application). It was evaluated the diameter at breast height (DBH), the plant height, the volume of wood with bark and certain macronutrient concentration in the leaves and soil. The eucalyptus without fertilization results in reduced growth of the plants. The development of the eucalyptus clone I-144 after 36 months old does not differ for rates and split-application of N and K 2 O